Efektivitas LKPD Ramah Disleksia Berbasis Visual untuk Mendukung Keterampilan Membaca Permulaan Siswa Kelas I Sekolah Dasar - Firda Nur Kumala; Nurul Istiq’faroh; Jeanies Marlene Saputro (Tumoutou Social Science Journal, 2026)
Low reading skills in dyslexic students are caused by symbol decoding obstacles and the mirror invariance phenomenon. This study aims to analyze the effectiveness of visual navigation-based dyslexia-friendly worksheets (LKPD) in improving beginning reading skills for first-grade students. Using a descriptive qualitative case study method, data were collected through observations and tests. Results showed a significant increase, with the subject's score rising from 50 to 85 (independent category). Visual navigation features and white space optimization effectively minimized symmetrical letter perception errors. The study concludes that these visual-based worksheets are a practical solution for overcoming specific literacy barriers while fostering learning independence in inclusive school.